Biocompatibility of composites based on chitosan, apatite, and graphene oxide for tissue applications. Issue 6 (21st February 2018) - Solìs Moré, Yaimara; Panella, Gloria; Fioravanti, Giulia; Perrozzi, Francesco; Passacantando, Maurizio; Giansanti, Francesco; Ardini, Matteo; Ottaviano, Luca; Cimini, Annamaria; Peniche, Carlos; Ippoliti, Rodolfo
Abstract: Novel two‐dimensional films and three‐dimensional (3D) scaffolds based on chitosan (CHI), apatite (Ap), and graphene oxide (GO) were developed by an in situ synthesis in which self‐assembly process was conducted to direct partial reduction of GO by CHI in acidic medium. Physical–chemical characterization was carried out by optical microscopy, scanning electron microscopy (SEM), Fourier‐transform infrared spectroscopy, Raman spectroscopy, and X‐ray photoelectron spectroscopy. In vitro biological studies using murine fibroblast (MC3T3) and human neuroblastoma (SH‐SY5Y) cell lines were also performed. Cell growth and adherence on composites was also checked using SEM. Live and death staining by confocal microscope and 3–(4, 5‐dimethylthiazol‐2‐yl)‐5–(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium of the samples were investigated. The results confirmed the incorporation of both Ap and GO sheets, into CHI polymeric matrix. Furthermore, it was confirmed a physical integration between inorganic Ap and organic CHI and strong chemical interaction between CHI and GO in the obtained composites. SH‐SY5Y cell line showed preferential adherence on CHI/GO films surface while MC3T3 cell line displayed a good compatibility for all 3D scaffolds. This study confirms the biocompatibility of materials based on CHI, Ap, and GO for future tissues applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1585–1594, 2018.